2008
DOI: 10.1126/science.1156973
|View full text |Cite
|
Sign up to set email alerts
|

BSKs Mediate Signal Transduction from the Receptor Kinase BRI1 in Arabidopsis

Abstract: Brassinosteroids bind to the extracellular domain of the receptor kinase BRI1 to activate a signal transduction cascade that regulates nuclear gene expression and plant development. Many components of the brassinosteroid signaling pathway have been identified and studied in detail. However, the substrate of BRI1 kinase that transduces the signal to downstream components remains unknown. Proteomic studies of plasma membrane proteins lead to the identification of three homologous BR-signaling kinases (BSK1, BSK2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
706
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 619 publications
(722 citation statements)
references
References 25 publications
15
706
1
Order By: Relevance
“…In the BR signalling at the cell surface, BRASSINOSTEROID-SIGNALLING KINASES (BSKs), which are known to function as cytoplasmic protein kinases, dissociate from BRI1 receptor complexes upon BRs perception 42 . This dissociation allows BSKs to interact with BRI1 SUPPRESSOR 1 (BSU1) 42,43 , which is a protein phosphatase and inactivates BIN2 by dephosphorylation 43 . We revealed that the PM-localized LRR-RLK TDR is closely associated with GSK3s including BIN2.…”
Section: Discussionmentioning
confidence: 99%
“…In the BR signalling at the cell surface, BRASSINOSTEROID-SIGNALLING KINASES (BSKs), which are known to function as cytoplasmic protein kinases, dissociate from BRI1 receptor complexes upon BRs perception 42 . This dissociation allows BSKs to interact with BRI1 SUPPRESSOR 1 (BSU1) 42,43 , which is a protein phosphatase and inactivates BIN2 by dephosphorylation 43 . We revealed that the PM-localized LRR-RLK TDR is closely associated with GSK3s including BIN2.…”
Section: Discussionmentioning
confidence: 99%
“…Brassinosteroid signaling kinase 1 (BSK1) may be the first downstream component that is phosphorylated by BRI1, which then activates the protein phosphatase BSU1 that can dephosphorylate/inactivate BIN2 (a glycogen synthase 3 protein kinase), which is the kinase that phosphorylates the transcription factors BZR1 and BZR2/BES1. 11 As a result, dephosphorylation of the transcription factors is promoted, which allows them to move into the nucleus to up or downregulate the many genes that are controlled by BR signaling. 12,13 The Arabidopsis genome contains more than 600 receptor-like kinase homologues.…”
Section: Bak1 Is a Dual-specificity Kinasementioning
confidence: 99%
“…Our study has provided clear structural evidence to support the previous speculation [5] that the initial phosphorylation of the BAK1 activation loop locks BAK1 kinase in the active conformation. BAK1 in turn phosphorylates and fully activates the ligand-binding RLK, which phosphorylates downstream substrates for signal transduction and the development of the innate immune responses of plants [14,15].…”
Section: Dear Editormentioning
confidence: 99%